Does the millennial and non-millennial generations moderate the relationship between brand loyalty and brand experience? - Pebrianti, Wenny; Miranda, Ninda (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to examine the effect of brand experience on brand loyalty by mediating affective commitment and the millennial and non-millennial generation as moderating variables for Xiaomi smartphone users in Pontianak. The population in this study is the people of Pontianak who use Xiaomi brand smartphones. The number of samples in this study were 100 respondents using the sampling technique, namely non-probability sampling with purposive sampling method. The data analysis method used in this research is Partial Least Square (PLS). The results showed that brand experience had a positive and significant effect on brand loyalty. Brand experience has a positive and significant effect on affective commitment. Affective commitment has a positive and significant effect on brand loyalty. Furthermore, the results obtained that affective commitment mediates the effect of brand experience on brand loyalty. The test of the moderating effect of the millennial generation moderating the effect of affective commitment on brand loyalty has a positive and significant effect. In addition, the test of the moderating effect of the non-millennial generation moderating the effect of affective commitment on brand loyalty has a positive and significant effect